Potential vector switching in the evolution of Bursaphelenchus xylophilus group nematodes (Nematoda: Aphelenchoididae) - Noritoshi Maehara; Natsumi Kanzaki; Takuya Aikawa; Katsunori Nakamura (Ecology and Evolution, 2020)
Abstract To show the importance of vector switching of nematodes in the evolution of the Bursaphelenchus xylophilus group, we tested a hypothesis that “Bursaphelenchus doui (or its ancestor) was transferred by Acalolepta fraudatrix, Acalolepta sejuncta, and/or Monochamus subfasciatus (or their ancestral species) from broad‐leaved trees to conifers, switched vectors from these cerambycid beetles to Monochamus beetles in conifers, and then evolved into the common ancestor of Bursaphelenchus mucronatus and B. xylophilus.” We used a simple nematode‐loading method to beetles and produced 20 binary combinations of five B. xylophilus group species and four cerambycid beetle species in the tribe Lamiini. The affinity of the nematodes for the beetles was examined based on phoretic stage formation of the nematodes. Phoretic stages of B. doui appeared in all beetle species examined, namely Acalolepta luxuriosa, Psacothea hilaris, A. fraudatrix, and Monochamus alternatus, although the affinity of the nematode for M. alternatus was weak. This finding indicates that B. doui could switch vectors to conifer‐using Monochamus beetles after transfer by A. fraudatrix from broad‐leaved trees to conifers. We conclude that vector switching of nematodes could have potentially happened during the evolutionary history of the B. xylophilus group.